Termite mound soil based potting media: a better approach towards sustainable agriculture - Kathbaruah, Shiney; Bhattacharyya, Badal; Borkataki, Shimantini; Gogoi, Bhabesh; Hatibarua, Preeti; Gogoi, Sailen; Bhairavi, K. Sindhura; Dutta, Pranab (Frontiers in Microbiology, 2024)
Termite mound soils are known to possess unique physico-chemical and biochemical properties, making them highly fertile. Considering their rich nutrient content, the objective of the current experiment is to assess the physico-chemical properties and enzyme activities of termite mound based potting media and evaluate theirperformance for further exploration in floriculture. Potting media consisting of termite mound soil (TS) of a subterranean termite, Odontotermes obesus were prepared in 7 different combinations with garden soil (GS), sand (S) and farmyard manure (FYM) and a control (without termite mound soil), i.e.